2018
DOI: 10.5121/acij.2018.9101
|View full text |Cite
|
Sign up to set email alerts
|

Secured AODV Routing Protocol for the Detection and Prevention of Black Hole Attack in VANET

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Furthermore, it assures transmitting data through it by presenting the shortest path to the receiver node [29,46]. e victim node chooses that shortest path and sends the data packet; any malicious node may drop the message or misuse the message for its own [41,47,48]. Figure 9 depicts that Car K desires to submit messages to Car P and Car Q, but it has no routing path for those nodes.…”
Section: Black Hole Assaultmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it assures transmitting data through it by presenting the shortest path to the receiver node [29,46]. e victim node chooses that shortest path and sends the data packet; any malicious node may drop the message or misuse the message for its own [41,47,48]. Figure 9 depicts that Car K desires to submit messages to Car P and Car Q, but it has no routing path for those nodes.…”
Section: Black Hole Assaultmentioning
confidence: 99%
“…AOVD [28,47,61,63], in MANETs, AODV protocol, is used for on-demand routing purposes with reactive routing. In the AODV protocol, routing table is maintained to store the next node routing information, i.e., for the target location nodes, and each routing table is used for a specific time period.…”
Section: Ad Hoc On-demand Distance Vector (Aovd)mentioning
confidence: 99%
“…However, they concluded that the solution performed well without any evidence. Lachdhaf, Mazouzi & Abid (2018) [10] proposed an approach to detect and prevent blackhole attacks on a Vehicle Ad Hoc Network. They used Cyclic Redundancy Check 32-bit used as the hash function to store converted destination IP addresses in the Routing Request (RREQ) packet.…”
Section: A Specific Solutions For Blackhole Attacksmentioning
confidence: 99%
“…In VANET, the network is designed in an ad hoc manner in which different connecting devices and moving vehicles communicate wirelessly without preexisting communication infrastructure. Therefore, the lack of centralized management in VANET gives the vehicles the responsibility to play the role of a router forwarding traffic information from a source to a destination [4]. The vehicles use this information to become aware of the circumstances ahead or to collaborate with other vehicles to ensure safe operation.…”
Section: Introductionmentioning
confidence: 99%